Effect of petroleum-based oil on management of sigatoka leaf spot (Fusarium sp.) on banana (Musa sp.) (Current Horticulture, 2024)
A field experiment was conducted at farmers’ fields to find out the effect of different treatments against sigatoka leaf spot caused by Mycosphaerella spp. on banana (Musa sp.) during 2014-15 and 2015-16 at KVK, Burhanpur, Madhya Pradesh, India. The experiment was laid out in a randomized block design in three replications with nine treatments. There was minimum per cent disease severity index of sigatoka (13.57%) by the treatment T8, i.e. spraying of Hexaconazole (H) @ 0.05% + petroleum based oil (Benole) @ 1% with maximum yield (69.9 t/ ha), followed by treatment T7 Propiconazole(P) @ 0.05% + Petroleum based oil (Benole) @ 1% (67.33 t/ha) as compared with rest of the treatments.
Keywords: Fungicides; Sigatoka leaf spot; PDI; Yield; Economics